2019
DOI: 10.1080/14767058.2018.1520831
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes associated with trial of labor after cesarean in women with one versus two prior cesarean deliveries after a change in clinical practice guidelines in an academic hospital*

Abstract: Adoption of ACOG's TOLAC practice changes, specifically offering TOLAC to women with two prior cesareans even without a prior vaginal delivery, and offering induction of labor regardless of cervical favorability, may increase VBAC rates without increasing maternal or neonatal morbidity from TOLAC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 12 publications
1
9
0
2
Order By: Relevance
“…Results from studies that have been conducted regarding the safety and feasibility of TOLAC in women with two previous cesarean deliveries are presented in ►Table 6 and include the results of this investigation. 6,[8][9][10][11][12][13][14] Studies have compared the outcomes of TOLAC2 to those of TOLAC1, which is more commonly practiced and often encouraged. Other studies have compared outcomes of TOLAC2 to the clinical alternative of a third elective repeat cesarean delivery 6,11,13,14 and have demonstrated that a third cesarean delivery carries its own immediate maternal and neonatal risks, including uterine rupture, hysterectomy, need for blood product transfusion or relaparotomy, as well as adverse neonatal outcomes including neonatal intensive care unit admission and respiratory morbiditiy.…”
Section: Discussionmentioning
confidence: 99%
“…Results from studies that have been conducted regarding the safety and feasibility of TOLAC in women with two previous cesarean deliveries are presented in ►Table 6 and include the results of this investigation. 6,[8][9][10][11][12][13][14] Studies have compared the outcomes of TOLAC2 to those of TOLAC1, which is more commonly practiced and often encouraged. Other studies have compared outcomes of TOLAC2 to the clinical alternative of a third elective repeat cesarean delivery 6,11,13,14 and have demonstrated that a third cesarean delivery carries its own immediate maternal and neonatal risks, including uterine rupture, hysterectomy, need for blood product transfusion or relaparotomy, as well as adverse neonatal outcomes including neonatal intensive care unit admission and respiratory morbiditiy.…”
Section: Discussionmentioning
confidence: 99%
“…Our success rate for vaginal delivery of 67.3% is in line with the literature which found success rates between 62.8% and 74.6%. [8,[18][19][20][21]. The success of the trial of labor is an important point because cesarean sections during labor might be more morbid than elective cesarean sections [22].…”
Section: Predictive Factors For Successful Vaginal Deliverymentioning
confidence: 99%
“…The main strength of our study is that it included only patients with two previous cesarean and compared the two strategies in an intention to treat strategy. Most of the available studies for the management of patients with two previous cesarean sections compare the outcomes of women with one versus two previous cesarean sections deliveries [16,17,19,20,[24][25][26]. Few studies, even national ones, address this issue, as the strategy of allowing vaginal delivery after two cesarean sections is in the minority.…”
Section: Strengths and Weaknessesmentioning
confidence: 99%
“…Мировое сообщество единодушно признало попытку вагинальных родов после КС (англ. trial of labor after cesarean, TOLAC) [10][11][12][13], не исключая ее после двух и более КС [14], допуская преиндукцию/индукцию родов [15,16]. Пересмотренные отечественные клинические рекомендации расширили перспективы для родоразрешения через естественные родовые пути после КС [3,17].…”
Section: Introductionunclassified
“…Пересмотренные отечественные клинические рекомендации расширили перспективы для родоразрешения через естественные родовые пути после КС [3,17]. Чрезмерные, не всегда оправданные ограничения для консервативных родов после КС представляют не менее серьезные риски, сопряженные с третьим и более абдоминальным родоразрешением [14].…”
Section: Introductionunclassified